Kinetic Hydration Heat Modeling for High-Performance Concrete Containing Limestone Powder - Xiao-Yong Wang (Advances in Materials Science and Engineering)
Limestone powder is increasingly used in producing high-performance concrete in the modern concrete industry. Limestone powder blended concrete has many advantages, such as increasing the early-age strength, reducing the setting time, improving the workability, and reducing the heat of hydration. This study presents a kinetic model for modeling the hydration heat of limestone blended concrete. First, an improved hydration model is proposed which considers the dilution effect and nucleation effect due to limestone powder addition. A degree of hydration is calculated using this improved hydration model. Second, hydration heat is calculated using the degree of hydration. The effects of water to binder ratio and limestone replacement ratio on hydration heat are clarified. Third, the temperature history and temperature distribution of hardening limestone blended concrete are calculated by combining hydration model with finite element method. The analysis results generally agree with experimental results of high-performance concrete with various mixing proportions.